Pengaruh Lingkungan Kerja Fisik dan Lingkungan Kerja Non Fisik terhadap Produktivitas Kerja di SDN 05 MARUNDA - Ida Umarul Mufidah; Izhatullaili Izhatullaili (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
This study aims to determine the effect of the physical work environment and non-physical work environment on the work productivity of the workforce, using quantitative methods, the research was conducted on the workforce at SDN 05 Marunda, North Jakarta, DKI Jakarta Province. The sampling technique for this study was simple random sampling of 30 people. Data collection was carried out by distributing questionnaires, interviews and for the physical work environment variable, measurements were added using a measuring instrument. The data generated from the questionnaire were analyzed using a multiple linear regression statistical test, while the results of measurements with measuring instruments were calculated and compared with the stipulated values in the Minister of Manpower Regulation Number 5 of 2018 concerning Occupational Health and Safety in the Work Environment. The research results from the hypothesis test obtained the F count > F table (23.160 > 3.32) and a significance value of 0.000 <0.05, it can be concluded that the third hypothesis is accepted by the physical work environment (X1) and non-physical work environment (X2) simultaneously effect on work productivity (Y). The second hypothesis is also accepted, there is an influence of the non-physical work environment (X2) on work productivity (Y), this is based on the t test obtained t count > t table (4.413 > 2.052) and a significance value of 0.0000 <probability 0.05. However, the first hypothesis is rejected, the value of t count <t table (-1.251 <2.052) and a significance value of 0.222 > probability 0.05, it can be concluded that there is no effect of the physical work environment (X1) on work productivity (Y).